The Great Silence, 1918-1920 : Living in the Shadow of the Great War - Nicolson, Juliet (Bath Windsor, 2010)
Peace at last, after Lloyd George declared it had been 'the war to end all wars', would surely bring relief & a renewed sense of optimism. But this assumption turned out to be misplaced as people realised that the men they loved were never coming home.
Include Illustrations and Bibliography.
Living in the Shadow of the Great War.
Keywords: Great Britain -- Social conditions